The Effect of Transaction Digitization and Lifestyle Orientation on Student Financial Management with Financial Literacy as a Moderation Variable - Baderi, Rahmawati; R. Pandin, Maria (Journal of Economics, Assets, and Evaluation, 2026)
This research seeks to examine the effect of transaction digitalization and lifestyle orientation on students’ financial management, as well as to assess the moderating role of financial literacy in this relationship. The investigation implements a quantitative research framework utilizing survey driven data collection. Data were collected through the distribution of Likert-scale questionnaires to selected respondents using a purposive sampling technique. The data collected were then processed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software support. The findings indicate that transaction digitalization has a positive and significant influence on students’ financial management. This indicates that the convenience and features offered by digital transaction services are able to help students in regulating, monitoring, and controlling their financial conditions. On the other hand, lifestyle orientation has a negative and significant effect on student financial management, which shows that consumptive lifestyle tendencies can hinder students’ ability to plan and control finances effectively. Meanwhile, financial literacy has not been empirically proven to moderate the effects of transaction digitalization and lifestyle orientation on students’ financial management. The findings further indicate that students’ financial management is primarily shaped by the intensity of digital transaction usage and lifestyle orientation, while financial literacy lacks a moderating role in the connection between these determinants and students’ financial management in contemporary digital times.